2016
DOI: 10.3906/sag-1506-49
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation in patients immobilized by a rigid collar: a comparison of GlideScope and an intubating laryngeal mask airway*

Abstract: Background/aim: Intubation must be rapidly performed with the utmost care in cervical trauma patients. We present the first comparison of GlideScope and an intubating laryngeal mask airway (ILMA) regarding insertion and intubation times, intubation success rates, mucosal damage, need for optimization maneuvers, effects on hemodynamic changes, and postoperative minor complications in a simulated cervical injury with a Philadelphia cervical collar. Materials and methods:Ethics committee approval and patient cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…success rates), rather than safety (cervical spine movement). Tracheal intubation through an LMA® Fastrach™ (Teleflex Medical Europe Ltd., Athlone, Ireland) is associated with similar success rates when compared with McCoy laryngoscopy (Penlon, Oxford, UK), the perilaryngeal airway (CobraPLA®; Engineered Medical Systems, Indianapolis, IN, USA) or LMA CTrach™ (Teleflex Incorporated) or Glidescope® (Verathon, Bothell, WA, USA) [28–31], lower success rate when compared with C‐MAC® (Karl Storz SE & Co. KG, Tuttlingen, Germany) [32], and greater success rate than tracheal intubation through a LMA Classic™ (Teleflex Incorporated) [33]. There were no clinically important differences between other supraglottic airway devices and means for achieving tracheal intubation [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…success rates), rather than safety (cervical spine movement). Tracheal intubation through an LMA® Fastrach™ (Teleflex Medical Europe Ltd., Athlone, Ireland) is associated with similar success rates when compared with McCoy laryngoscopy (Penlon, Oxford, UK), the perilaryngeal airway (CobraPLA®; Engineered Medical Systems, Indianapolis, IN, USA) or LMA CTrach™ (Teleflex Incorporated) or Glidescope® (Verathon, Bothell, WA, USA) [28–31], lower success rate when compared with C‐MAC® (Karl Storz SE & Co. KG, Tuttlingen, Germany) [32], and greater success rate than tracheal intubation through a LMA Classic™ (Teleflex Incorporated) [33]. There were no clinically important differences between other supraglottic airway devices and means for achieving tracheal intubation [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Performed with a Miller or Macintosh blade laryngoscope in many cases can be difficult to perform or completely ineffective. This is particularly the case when intuba- tion is performed by people without direct laryngoscopy experience [8][9][10][11], during cardiopulmonary resuscitation, when continuous chest compression is performed [12][13][14], in the case of intubation of patients with immobilized cervical spine [15][16][17], or patients with difficult airways [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Özdil S et al [12] compared ILMA and Glidecope for intubation of patients with rigid neck collar and demonstrated that success rate was 96% in both groups, both insertion and intubation times were longer for ILMA (21.9 ± 6.5 s and 48.4 ± 11 s), total time for intubation was longer for ILMA (85.6 ± 13 s), damage to mucosa was higher with ILMA, and both devices increased HR and blood pressure.…”
Section: Discussionmentioning
confidence: 99%